A framework of computer-based screening test using learning theories and design guidelines for early detection of Dyslexia - Nik Siti Fatima Nik Mat
Dyslexia is a specific learning disability that affects people of all backgrounds globally without prejudice. Most primary learning institutions in Malaysia applied paper-based screening tools to identify dyslexic children before they are referred to psychologists for further tests to identify their disability. The problems with paper-based screening test were cumbersome, time consuming and not very attractive. Although there were studies done in computer-based screening tests, results are still limited and applications are not designed for dyslexic children. The objectives of this study are to construct the framework and design as well as to evaluate the classification performance of dyslexic children. The proposed framework consists of an integrated design guideline, learning theories and assessment modules specifically formulated for screening dyslexic children at an early age. The methodology in this study involved five phases; i) theoretical study, ii) conceptual framework design, iii) proposed framework validation, iv) data collection screening, and iv) evaluation. The proposed framework was validated using prototyping approach. The evaluation was done by expert reviews and user acceptance study. The evaluation study was conducted by implementing a screening test to school children from Showme Kids School and Ampang Dyslexia School. The results of the evaluation showed that the application implemented was highly effective. Overall, 97.2% of 49 respondents agreed and accepted the application. In addition, it has also been proven that 148 classification result of the discrimination obtained 97.96% of accuracy. Hence, the application is well accepted whereby it is expected to act as an early detection dyslexia screening tool. As a conclusion, the proposed framework was able to discriminate between dyslexic and non-dyslexic children.